Wpływ anglojęzycznych tłumaczeń literatury grozy w 1990–1995 na kształtujące się po 1989 roku polskie realizacje gatunku - Mazurkiewicz, Adam (Zagadnienia Rodzajów Literackich, 2025)
The article is devoted to the formation of a new horizon of expectations towards horror literature, which appeared on the literary market and was influenced by translations between the years 1989–1995. At the same time, it was a period of economic transformation from an economic model of top-down control to one subordinated by the rules of the free market, in which the book(resp. literature) became a commodity, subordinated like any other to the market mechanisms of supply and demand. As a result, the book market was dominated by books that were not always artistically valuable, but widely read (this explains the popularity of second-rate authors in Poland, who had their own publishing series in publishing houses).The beginning of the transformation in the understanding of the essence of horror fiction was associated with the appearance on the Polish book market of translations from English-language literature, which dominated popular literature of the time. Even then, it was also possible to notice that the translations — dominating the readers’ stock market — could not be reduced to a single, dominant concept of horror fantasy. This is because it appeared on the Vistula with the following problematic and thematic trends: (1) emphasizing corporeality as a source of horror, resulting from the “adventures of the body” — both non-normative, disciplined, and subjected to variously motivated interference; (2) emphasizing the uncanny as an immanent feature of existence; (3) problematizing the issue of the species hegemony of man treated in traditional culture as the “crown of creation”; (4) rooted in locality and finding sources of horror in it. The problematic and thematic trends of horror stories listed here, which can be found in the translations from 1989–1995, dominated Polish literature to such an extent that it — insofar as it appeared on the readers’ market — copied proven (in terms of plot, but also marketing) patterns, inspired by Western translations.